Polarization Over Vaccination: Ideological Differences in Twitter Expression About COVID-19 Vaccine Favorability and Specific Hesitancy Concerns. (September 2021) - Jiang, Xiaoya; Su, Min-Hsin; Hwang, Juwon; Lian, Ruixue; Brauer, Markus; Kim, Sunghak; Shah, Dhavan
Vaccine hesitancy has been a growing public health issue, but during COVID-19, understanding vaccine hesitancy and promote vaccine favorability takes on a troubling immediacy. With the growing political polarization on scientific issues, the COVID-19 vaccine-related sentiment has recently been divided across ideological lines. This study aims to understand how vaccine favorability and specific vaccine-related concerns including possible side effects, distrust in medical professionals, and conspiratorial beliefs concerning COVID-19 vaccines were articulated and transmitted by Twitter users from opposing ideological camps and with different follower scopes. Using a combination of computational approaches, including supervised machine-learning and structural topic modeling, we examined tweets surrounding COVID-19 vaccination ( N = 16, 959) from 1 March to 30 June 2020. Results from linear mixed-effects models suggested that Twitter users high on conservative ideology and with a standard instead of large follower scope tend to express less favorable vaccine-related sentiments and talk more about vaccine side effects, distrust of medical professionals, and conspiracy theories. There is also an interaction effect where liberals with large follower scope expressed the least amount of distrust of medical professionals, whereas extreme conservatives expressed greater distrust for health professionals, regardless of their follower scope. Finally, structural topic modeling revealed distinct topical focuses among liberal and conservative users. Theoretical and practical implications for leveraging social media in effective health communication practice were discussed.